2015
DOI: 10.1159/000441153
|View full text |Cite
|
Sign up to set email alerts
|

DWI Lesion Patterns Predict Outcome in Stroke Patients with Thrombolysis

Abstract: Background: Lesion patterns may predict prognosis after acute ischemic stroke within the middle cerebral artery (MCA) territory; yet it remains unclear whether such imaging prognostic factors are related to patient outcome after intravenous thrombolysis. Aims: The aim of this study is to investigate the clinical outcome after intravenous thrombolysis in acute MCA ischemic strokes with respect to diffusion-weighted imaging (DWI) lesion patterns. Methods: Consecutive acute ischemic stroke cases of the MCA territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Since the deep MCA territory is crossed by the corticospinal tract [ 22 ] and is prone to damage by poor collateral flow [ 23 ], this area may be susceptible to motor deficits, regardless of rt-PA thrombolysis. In some reports, patients with deep white matter or basal ganglia infarction have suffered from bad outcomes after thrombolysis or endovascular therapy [ 7 , 22 , 23 ]. Thus, even small lesions in this area could be critical to the outcome of mild ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the deep MCA territory is crossed by the corticospinal tract [ 22 ] and is prone to damage by poor collateral flow [ 23 ], this area may be susceptible to motor deficits, regardless of rt-PA thrombolysis. In some reports, patients with deep white matter or basal ganglia infarction have suffered from bad outcomes after thrombolysis or endovascular therapy [ 7 , 22 , 23 ]. Thus, even small lesions in this area could be critical to the outcome of mild ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) with diffusion-weighted imaging (DWI) is superior to computed tomography (CT) for early detection of hyperacute and small ischemic lesions. Pretreatment DWI lesion patterns may be helpful in predicting clinical outcome in patients with acute ischemic stroke [ 6 , 7 ]. Steno-occlusive lesions of the cerebral artery are associated with unfavorable outcomes in patients with minor strokes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, lesion volumes have shown only moderate correlation with long-term clinical outcome measures 2 . Recent studies 5,7,28,29 demonstrated that models taking into account accurate lesion topography (in addition to lesion volume) improve stroke prediction outcome and identify patients likely to benefit most aggressive reperfusion intervention and personalized rehabilitation therapies. Indeed, when deciding whether to perform reperfusion therapy, it is important to confirm whether the lenticulostriate arteries are involved in the ischemia 16,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Index lesions are the most crucial factors, as they directly determine treatment and prognosis. Many retrospective studies require MRI information extracted from index lesions to analyze the association between lesion characteristics and clinical outcomes [19, 20].…”
Section: Discussionmentioning
confidence: 99%